2011
DOI: 10.1037/a0021884
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion and relationship maintenance: The moderating roles of conscientiousness and gender.

Abstract: Should intimates respond to their interpersonal mistakes with self-criticism or with self-compassion? Although it is reasonable to expect self-compassion to benefit relationships by promoting self-esteem, it is also reasonable to expect self-compassion to hurt relationships by removing intimates’ motivation to correct their interpersonal mistakes. Two correlational studies, 1 experiment, and 1 longitudinal study demonstrated that whether self-compassion helps or hurts relationships depends on the presence vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(118 citation statements)
references
References 108 publications
6
101
0
2
Order By: Relevance
“…Self-Compassion. Neff's (2003b) 26-item Self-Compassion Scale is commonly used to measure self-compassion (Akin & Eroglu, 2013;Baker & McNulty, 2011;Neff & Beretvas, 2013). In 2011 Raes and colleagues developed and tested a 12-item short version of this scale (Raes, Pommier, Neff, & Van Gucht, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Self-Compassion. Neff's (2003b) 26-item Self-Compassion Scale is commonly used to measure self-compassion (Akin & Eroglu, 2013;Baker & McNulty, 2011;Neff & Beretvas, 2013). In 2011 Raes and colleagues developed and tested a 12-item short version of this scale (Raes, Pommier, Neff, & Van Gucht, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…In these research it was found that self-compassion is linked positively to social relationship, emotional intelligence, self-determination (Neff, 2003a), social support (Akın, Kayış, & Satıcı, 2011), psychological well-being (Akın, 2008a), learning-approach goals (Akın, 2008b), life satisfaction, social relatedness (Neff, 2003b), reflective and affective wisdom, personal initiative, curiosity and exploration, optimism, positive affect, extraversion, agreeableness, conscientiousness (Baker & McNulty, 2011;, and relational-interdependent self-construal (Akın & Eroglu, 2013). Conversely, the other studies have showed that selfcompassion is negatively related to interpersonal cognitive distortions (Akın, 2010a), loneliness (Akın, 2010b), submissive behavior (Akın, 2009), automatic thoughts (Akın, 2012), depression, anxiety, rumination, thought suppression (Neff, 2003b), performance-approach/avoidance goals (Akın, 2008b), internet addiction (Iskender & Akın, 2011), social anxiety, fear of negative evaluation (Werner et al, 2012), and neuroticism .…”
Section: *) Self-compassionmentioning
confidence: 99%
“…This effect is amplified when self-compassion is combined with high conscientiousness, motivating individuals to attend to strife and fix relational mistakes (Baker & McNulty, 2011). It naturally follows that mindfulness and common humanity correlate positively with relational-interdependence of the self-construal, or defining oneself in terms of one's close others, and feelings of seclusion have a strong negative correlation with self-compassion (Akin & Eroğlu, 2013).…”
Section: Self-compassionmentioning
confidence: 99%
“…Because self-compassion is an important predictor of an individual's reaction to interpersonal conflict, it could play an equally important role in cyberbullying involvement (Baker & McNulty, 2011;Neff, 2004;Petersen, 2014). By identifying an association between self-compassion and cyberbullying, the current research could pave the way for the development of more effective interventions to eliminate cyberbullying behaviors, just as Neff et al (2007) demonstrated that raising self-compassion could improve one's psychological well-being.…”
Section: Current Studymentioning
confidence: 99%